IMPLEMENTASI EKATE.APP SEBAGAI MEDIA PEMBELAJARAN PADA MATERI EKONOMI KREATIF DI TINGKAT SEKOLAH MENENGAH ATAS - Dwiasa Sambhawa Dharma; Sauca, Dhinar Mawanti (Widya Aksara : Jurnal Agama Hindu, 2025)
Information and communication technology in learning has a role as an intermediary in the implementation of knowledge transfer without completely eliminating the initial learning model that takes place in face-to-face classes. The use of technology as a creative and interesting learning medium, it is important for teachers to pay attention to the syllabus and learning outcomes of the content and materials to be used. The purpose of this study is to find out the results of the implementation of the "Ekonomi Kreatif Tourism (EKATE.App)" learning media product in economics class XI (Phase F) which discusses the creative economy. In accordance with the purpose of the research, this research is designed as research and development (R&D). The development model used is based on the ADDIE model. The stage that goes through the product implementation process. Implementation trial by 35 Phase F (Class XI-11) students of SMA Negeri 1 Talun. The implementation completed by the researcher found that the results of the trial obtained a percentage of 88% which explained that the tourism creative economy (EKaTe.App) learning media product is feasible and effective to be used in the economic learning process. EKaTe.App proven to improve the understanding and learning outcomes of creative economy students in Grades XI-11 of SMA Negeri 1 Talun. This media offers an innovative learning experience with interactive features, increases motivation, and supports independent and group learning. Easy access via smartphones allows students to learn at any time. Positive responses from students and teachers show its effectiveness as an innovative alternative to economics learning in schools.